Engineering complex systems with models and objects - Oliver, David W (Mc Graw Hill, 1997)
"In this book you'll learn how to make the right selection of alternative designs or architectures; produce executable structure models that can be transformed into alternative views and verified by computer; formulate a design that meets all functional and performance requirements and is both feasible and optimal for the marketplace; accurately assess information made available to the systems engineering team; perform trade-off analyses that enhance decision making; create, build, and test a plan; and tailor the six-step engineering process to fit specific business environments." "This scalable systems engineering approach can be easily adapted to model products, services, businesses, processes, and plans. Guidelines are included on how to improve training capability in your company ... select and develop tools for automation ... build highly efficient infrastructure ... and customize the system engineering process to commercial or aerospace projects. In addition, the authors clearly distinguish management tasks from the technical tasks of systems engineers."--BOOK JACKET.